Effect of Consulting on Microcredit Repayment in Korea - Yoon Hae Oh (KDI Journal of Economic Policy, 2015)
This study examines the effect of a one-on-one outsourced pre-lending consulting service on the repayment behavior of microcredit borrowers in Korea with administrative data from the Smile Microcredit Bank. A random change in the cut-off loan amount for mandatory consulting is utilized as an identification strategy. This three-day pre-lending business consulting service is effective in encouraging repayment behavior of existing businesses but it has no significant effect on start-up loans. The effectiveness of the consulting service in deterring delinquency with regard to existing loans is greater among male borrowers than among females.
Keywords: D1; G21; J1; L3; N25; 330; Microcredit; Nonfinancial Service; Consulting; Loan; Repayment; Arrear